TRANSBOUNDARY HAZE POLLUTION ACT 2014 DAN PROBLEMATIKA KEBAKARAN HUTAN DI INDONESIA - Fitriani, Ifa Latifah (UIN Sunan Kalijaga Yogyakarta, 2014)
Transboundary Haze Pollution Act 2014 is a law established by the Singapore to combat air pollution caused by forest fires in Indonesia that have continued to occur every year. Moreover, the substance of these rules could potentially enter the Indonesian jurisdiction. It is possible because there are extra-territorial arrangements, governing the imposition of criminal or civil liability for the perpetrators of the causes of air pollution in Singapore. the imposition of civil and criminal liability will be applied for every entity both inside and outside of Singapore who contributes to any haze pollution in Singapore. Therefore, this rule is questioned by Indonesia, according to the ASEAN Agreement on Transboundary Haze Pollution itself did not regulate the imposition of criminal-civil liability through the rigid application of the principle of extraterritoriality.